368 Successful Use of Plasmapheresis for Hyperbilirubinemia in a Premature Newborn While on Extracorporeal Membrane Oxygenation. (11th January 2018) - Belousova, Tatiana; Tong, Yi Tat; Conyers, Jeffrey; Klein, Kimberly; Bai, Yu; Tint, Hlaing; Castillo, Brian
Abstract: Objectives: A premature baby girl with a complicated hospital course developed RSV pneumonitis at 2 months of age for which she was placed on extracorporeal membrane oxygenation (ECMO). In spite of earlier phototherapy, bilirubin was steadily increasing and reached 50.4 mg/dL with concern for bilirubin induced neurologic dysfunction. Exchange transfusion was not recommended due to patient instability and risk of significant deterioration while on ECMO. Plasma exchange (PLEX), although not a recognized as a category treatment option for hyperbilirubinemia by the American Society for Apheresis (ASFA), was suggested as an alternative management option. We present a case of successful management of hyperbilirubinemia by PLEX in a premature baby while on ECMO. Methods: PLEX was done via connection with the ECMO circuit. Parameters were appropriately adjusted for the small body weight and ECMO circuit. For the procedure we used all fresh frozen plasma with plasma volume exchange between 1.0 and 1.3. We also primed the apheresis machine with packed red blood cells to minimize volume loss in tubing systems. Results: A total of three procedures were done daily and resulted in rapid improvement and stabilizing of bilirubin level. The procedure was very effective and well tolerated. Despite stabilizing the bilirubin level, the patient ultimately expired due to her underlying medical condition. Conclusion: This case is unique because of the use of PLEX on premature baby of 3.4 kg, but also because of use of ECMO as the point of access. In addition this case highlights that PLEX can be successfully used in this unique patient population as well as for management of hyperbilirubinemia in this patient group. The use of PLEX should be considered in premature babies complicated by extreme hyperbilirubinemia that are not candidates for standard treatment options to prevent further worsening of kernicterus and gain fast correction of bilirubin values.